Adobe Photoshop CS2 visual encyclopedia - Romaniello, Stephen (Wiley, 2006)
If you prefer to see what things look like and how to perform a task, instead of just being told, this is your ideal A to Z reference. Part I shows every Photoshop CS2 tool and how to use it. Part II provides step-by-step instructions for more than 130 key tasks and techniques. Both are arranged alphabetically and illustrated in full color. It's the ultimate Visual resource - you'll see!